UJI EFEKTIVITAS EKSTRAK ETANOL DAUN JAMBU BIJI MERAH (Psidium guajava L.) DALAM MENGHAMBAT PERTUMBUHAN BAKTERI Porphyromonas gingivalis PENYEBAB PERIODONTITIS - Qonitah Nur Aslamiyah; Mudyawati Kamaruddin; Steffi Triany Arnov (Universitas Muhammadiyah Semarang, 2023)
Background: Chronic periodontitis is a disease of the oral cavity that is often complained by almost the entire population of the world. Prevalence Porphyromonas gingivalis in chronic periodontitis, which reached 96.2%. Mechanical treatment that can be given are scaling, root planing, curettage, and administration of antibiotics. Red guava leaves (Psidium guajava L.) can act as an antibacterial because it contains several active compounds such as tannins, flavonoids and saponins.Method: This study was a laboratory experimental study with a post-test only group design. The red guava leaf extract sulution concentrations used were 2%, 5%, 10%, 15% and 20%. The Phorpyromonas gingivalis bacteria were the dependent variable in this study.Results: Ethanol extract of red guava leaves concentrations of 2%, 5%, 10%, 15% and 20% is effective in inhibiting the growth of bacteria Porphyromonas gingivalis, with 20% having the largest inhibition zone.Conclusion: Based on this research, it can be concluded that the higher the concentration of the ethanol extract of red guava leaves (Psidium guajava L.) used, the larger the diameter of the inhibition zone formed.